Substantial loss of T cells upon lymphocyte isolation from heparin-anticoagulated peripheral blood - Berg, Victoria; Ross, J. Alexander; Dampmann, Maria; Küppers, Ralf; Budeus, Bettina (Frontiers in Immunology, 2025)
Analysis of lymphocytes usually involves the usage of blood anticoagulants, with the type of anticoagulant often determined by clinical routines, without testing which anticoagulant is ideal for the research question. We systematically compared the effects of ethylenediaminetetraacetic acid (EDTA) and heparin anticoagulation on recovery and composition of peripheral lymphocyte populations. This comprehensive analysis of the effect of heparin and EDTA on recovery of different lymphocyte subsets has, to our knowledge, not been performed previously. On average, the recovery of lymphocytes is lower in heparin-treated samples. This is due to a loss of T cells, as the absolute numbers of T cells is reduced by 38% in heparin-treated samples compared to EDTA-treated samples, whereas there was no significant loss of B cells observed in the heparin-treated samples. Several T cell subsets, such as memory T cell subsets, are significantly affected. We analysed different steps of the lymphocyte isolation protocol to clarify in which step cells are lost. Losses during several isolation steps showed biases in cell composition, and a significant amount of cells may be lost, e.g. during density gradient centrifugation. However, these losses were generally similar in EDTA- and heparin-treated samples, arguing for an additional mechanism of cell loss. In conclusion, isolation of mononuclear cells from peripheral blood with heparin as anticoagulant causes a partial loss of T cells, with particular subsets preferentially affected, so that there is a risk that the composition of the lymphocyte compartment may be inaccurately assessed when using heparin-treated blood.